2019
DOI: 10.3329/aajbb.v4i1.64925
|View full text |Cite
|
Sign up to set email alerts
|

Farmers’ awareness on use of ICT in farm practices

Abstract: The main purpose of the study was to understand the extent of awareness of farmers on use of ICT in farm practices. At the same time, important factors were identified those could contribute to farmers‟ awareness on use of ICT. The study was conducted in the existing CIG of Ishwarganj upazila in Mymensingh district. Data were collected from 110 CIG farmers in the selected upazila during the period from 03 October to 05 November, 2018 by using a pre-tested structured interview schedule. Farmers‟ awareness was m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 6 publications
0
1
0
Order By: Relevance
“…This implies that mobile phones, radio and television are the most used ICT tools. According to Hasan et al, (2019), farmers are slowly becoming more aware of the use of smartphones. Research conducted by Ayim et al, (2020), Ekeanya et al, (2018), and indicated that televisions, mobile phones, and radios are the most commonly used ICT tools in the agricultural sector.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…This implies that mobile phones, radio and television are the most used ICT tools. According to Hasan et al, (2019), farmers are slowly becoming more aware of the use of smartphones. Research conducted by Ayim et al, (2020), Ekeanya et al, (2018), and indicated that televisions, mobile phones, and radios are the most commonly used ICT tools in the agricultural sector.…”
Section: Resultsmentioning
confidence: 99%
“…The current system of education in formal schools where students are taught basic ICTs could also be a reason for this situation. According to Hasan et al, (2019), older individuals are less likely to use ICT, which serves as a hindrance to the adoption of ICT. The finding agrees with Khalak et al, (2018) that age is an important determinant of respondents' likelihood of having access to ICTs.…”
Section: Determinants Of Accessibility To Icts By Cocoa Farmersmentioning
confidence: 99%
See 2 more Smart Citations
“…While COVID-19 outbreak was well-understood by 100% farmers, the importance, benefits and utilization of AI in agriculture or agri-food supply chain was acknowledged by only 22.83%. Only 39.59% of the farmers have the understanding that the application of AI in agriculture or agri-food supply chain will be beneficial, which revealed the unawareness among most of the farming community about the technological advancement which is supported by earlier studies [112][113][114][115][116][117].…”
Section: The Socio-demographic Data and Awareness Of Farmersmentioning
confidence: 99%